Prevalence of Myocardial Infarction with Non-Obstructive Coronary Arteries in Western Nepal - Kafle, Ram Chandra; Jha, Girija Shankar; Sharma, Dibya; Alurkar, Vijay Madhav (Nepalese Heart Journal, 2020)
Background and Aims: It is well known that ST segment elevation myocardial infarction results from complete occlusion of a coronary artery supplying that area. However, in up to 15% of patients with clinical diagnosis of myocardial infarction, early angiography reveal either non-obstructive or normal coronary artery. This subgroup of disease, myocardial infarction (MI) with non-obstructive coronary arteries (MINOCA), represent a diagnostic and therapeutic challenge to clinicians. We aimed to determine prevalence and clinical profile of patients with MINOCA in current study.Methods: This is a retrospective, observational study conducted in cardiology department of Manipal Teaching Hospital, Pokhara, Nepal from 6th April 2014 to 5th April 2019. Patients with age ≥18 years and clinically diagnosed acute myocardial infarction who underwent coronary angiography without prior use of thrombolytic agents were selected. Data were analyzed using the software SPSS for windows version 18.Results: A total of 177 patients’ underwent early coronary angiography without prior use of thrombolytic agent. The prevalence of MINOCA was 13.5% (n=24) in our study population. MINOCA patients were younger (p